Modern societal impacts of the model minority stereotype - Hartlep, Nicholas Daniel; IGI eBooks; IGI Global (Hershey, Pennsylvania (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA) : IGI Global, 2015)
"This book highlights current research on the implications of the model minority stereotype on American culture and society in general as well as Asian and Asian-American populations by offering an in-depth analysis of current social issues, media influence, popular culture, identity formation, and contemporary racism in American society"--Provided by publisher.
"I can't afford for you to flunk": positive Asian stereotypes and supportive communication for Asian college students / Chau-Sa T. Dang, Susan L. Kline -- Spelling otherness: Indian Americans as the "new model minority" / Sanjukta Ghosh -- The intersection of the Asian American model minority myth and sports: the "Linsanity" narrative / Teresa A. Mok, David W. Chih -- From model minority to "angry Asian man": social media, racism, and counter-hegemonic voices / Tanya Grace Velasquez -- "You speak good English": stereotyping of the perpetual foreigner / Rong Chang, Sarah L. Morris -- Thwarting or embodying model minority stereotypes: an alternative look at adjustment of Asian international students in American higher education / Eunyoung Kim, Katherine C. Aquino -- Heritage language learning for contesting the model minority stereotype: the case of Korean American college students / Hyun-Sook Kang -- "I hate my own race. the teachers just always think we're smart": re-conceptualizing the model minority stereotype as a racial epithet / Sophia Rodriguez -- A double-edged sword: side effects of the model minority stereotype on Asian immigrants in the U.S. / Bita H. Zakeri -- Model minority: normative exception and/or example? / Karen Sy de Jesus -- Narratives of Asian/American educators: a case study of resistance and rhetoric / Trish Morita-Mullaney, Michelle C. S. Greene -- The model minority narrative and its effect on Asian American identity and social status / Guy Lowe.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Description based on title screen (IGI Global, viewed 03/14/2015).
Keywords: Asian Americans -- Social conditions; Asian Americans -- Race identity; Asian Americans -- Education; Model minority stereotype -- United States; Racism -- United States; Asian Americans in popular culture; Mass media -- Social aspects -- United States; United States -- Race relations; United States -- Ethnic relations; United States -- Social conditions -- 1980-; Cultural formation; Discrimination; Ethnic studies; Media and racism; Popular culture; Self-identity and racism; Social justice; Electronic books